MOTIF DAN KEPUASAN MAHASISWA ILMU KOMUNIKASI UNJ ANGKATAN 2019 DALAM MENGGUNAKAN MEDIA SOSIAL INSTAGARAM - Firdausi, Tasya Indah; Putri, K. Y.S. (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2021)
Social media has various types and of course, has different functions and ways of working. Someone uses social media, of course, because there is something they are looking for (motive), and everyone has different motives for using social media, and this is influenced by 4 indicators, namely, information, social interactionl, entertainment, and personal identity. Instagram is a place where you can easily share photos, videos, and interact with other people through online networks. This study uses a quantitative approach with 45 samples and uses a random sampling technique. The data was collected by distributing questionnaires in the form of google form. The data analysis technique used was coding (Likert scale), testing the validity and reliability using SPSS version 21, and calculating the average (mean). From the results obtained, it shows that the motive of information is the motive most sought by students in using Instagram, social satisfaction is the highest satisfaction obtained by students in using Instagram. And the value of the biggest gap between motive and satisfaction is the information indicator.